A Study of Non-Performing Assets of Commercial Banks in India: Impact of Non-Performing Assets on the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Banks play an important role in the economic development of a country. The Indian banking sector has been facing serious problem of growing Non-performing assets(NPA's). The NPA growth has a direct impact on the profitability of the banks. Banks are growth driver and the banking business is exposed to many risks, such as credit risk, liquidity risk, interest rate risk, market risk, operational risk and management risk. But the major risk faced by banks these days is high level of NPA's. The financial position of the banks is based on the level of recovery of loans and its level of Non-Performing Assets. Reduced NPA's leads to impression that banks have strengthened their credit appraisal processes and increased NPA's leads to creation of more provisions which will reduce profitability of the banks. This paper makes an attempt to study the level of Non-Performing assets of the commercial banks in India. To improve the profitability and efficiency of the banks it is the need of the hour to reduce and control the level of NPA's, so that negative impact on the economy is minimal.